Method for making fire resistant and / or flame retardant cable

Through the method of impregnating nonwoven fiber materials and hot extrusion protective polymer sleeves in the geological polymer composition, the complex and pollution problems of flame retardant cables in the prior art are solved, and rapid and economical production is achieved, ensuring the cable Mechanical properties and durability of the wire.

CN112117060BActive Publication Date: 2024-12-20NEXANS SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202010558386.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-20
Filing Date
2020-06-18
Publication Date
2024-12-20
Estimated Expiration
2040-06-18

AI Technical Summary

Technical Problem

The existing methods of manufacturing refractory cables are complex, discontinuous, and easily contaminated by geological polymer compositions, making it difficult to quickly and economically obtain flame retardant cables with good mechanical characteristics in industrial production.

Method used

Using a method of impregnating nonwoven fiber material with a geological polymer composition, a dry composite layer is formed by a coating-impregnation step, and the composite layer is applied around the elongated conductive element, combined with a hot extrusion protective polymer sleeve to form an efficient Manufacturing process.

Benefits of technology

Fast, easy to implement and economical flame retardant cable production is achieved, avoiding contamination of geological polymer compositions, and ensuring good mechanical properties and durability of the cable, especially in terms of flexibility and fire resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112117060B_ABST
    Figure CN112117060B_ABST
Patent Text Reader

Abstract

The invention relates to a method for manufacturing a cable comprising at least one elongated conductive element and at least one composite layer surrounding said elongated conductive element, said composite layer being obtained by at least one step of impregnation of a nonwoven fibrous material with a geopolymer composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing a cable comprising at least one elongated conductive element and at least one composite layer surrounding said elongated conductive element, said composite layer being obtained by at least one step of impregnation of a nonwoven fibrous material with a geopolymer composition.

[0002] It is typically, but not exclusively, applied to flame retardant and / or fire resistant cables intended for power transmission and / or data transmission, such as flame retardant and / or fire resistant electrical cables and / or safety optical cables, in particular halogen-free, capable of operating for a given length of time under fire conditions, but not being a fire propagator, nor a generator of significant amounts of smoke. These safety cables are in particular medium voltage power transmission cables (in particular from 6 to 45-60 kV) or low frequency transmission cables, such as control or signaling cables. Background Art

[0003] From WO 2016 / 099200 a method for manufacturing a fire-resistant cable is known, comprising the steps of: a step of preparing a geopolymer composition comprising sodium silicate, water, potassium hydroxide, aluminosilicate and polypropylene fibers; a step of wrapping a nonwoven paper tape around an assembly of copper conductors, a step of impregnating the copper conductor / nonwoven paper tape assembly in the previously prepared geopolymer composition by dip coating to form a composite layer surrounding the copper conductors, and then a step of hot extruding a protective polymer sheath. This is a long process, in particular due to the drying step, and cannot be carried out continuously. In addition, the constituent elements of the cable close to the composite layer based on geopolymer material can easily be contaminated by the geopolymer composition.

[0004] The object of the present invention is therefore to overcome some or all of the abovementioned drawbacks and to provide a method for manufacturing a flame retardant cable which is easy to implement, particularly easy to industrialize, economical and rapid, and which is capable of producing a cable having good mechanical properties, particularly in terms of flexibility and durability. Summary of the invention

[0005] The present invention firstly relates to a method for manufacturing a cable, the cable comprising at least one elongated conductive element and at least one composite layer surrounding the elongated conductive element, characterized in that the method comprises at least the following steps:

[0006] i) impregnating a non-woven fibrous material with a geopolymer composition so as to form a belt impregnated with said geopolymer composition,

[0007] ii) drying the impregnated tape obtained in step i) to form a dried impregnated tape, and

[0008] iii) applying said dried impregnated tape obtained in step ii) around a cable comprising at least one elongated conductive element so as to form said composite layer surrounding said elongated conductive element.

[0009] The method of the invention is rapid, easy to implement (especially on an industrial scale), economical and it ensures that fire-resistant and / or flame-retardant cables are obtained with good mechanical properties, especially in terms of flexibility and durability. Furthermore, the method of the invention makes it possible to avoid contamination of the constituent elements of the cable close to the composite layer by the geopolymer composition.

[0010] In step i), the nonwoven fibrous material is preferably in the form of tapes or strips.

[0011] Step i) can be performed manually or automatically, and is preferably performed automatically.

[0012] Step i) is preferably carried out by coating-impregnation and particularly preferably by pre-controlled coating.

[0013] Step i) can be performed, for example, using a coating device such as a coating die.

[0014] More specifically, step i) is carried out by passing the nonwoven fibrous material through a coating device such as a coating die, which is supplied with the geopolymer composition, in particular using a device such as a pump. This thus enables the desired amount of geopolymer composition to be distributed directly and evenly over the desired width of the material.

[0015] Step i) may in particular be a coating method known under the English term “tensioned web die coating”.

[0016] In a preferred embodiment of the present invention, the impregnation step i) is carried out at a temperature of from about 15°C to 90°C and particularly preferably from about 20°C to 40°C.

[0017] Step ii) consists in drying the impregnated tape obtained in the preceding step i).

[0018] Step ii) may be carried out at a temperature of at most about 120° C. and preferably at most about 110° C. A temperature of at most 120° C. and preferably at most 110° C. makes it possible to avoid hardening of the composition before step iii).

[0019] Step ii) may be performed at a temperature of at least about 50° C. A temperature of at least 50° C. may enable rapid drying to be promoted.

[0020] Step ii) is preferably carried out at a temperature of from about 70 to 115°C and particularly preferably from about 90 to 107°C.

[0021] Step ii) enables the geopolymer composition to be transformed from a liquid state into a semi-pasty state. More specifically, at the end of step ii), the geopolymer composition comprises at least one phase in the form of an aluminosilicate gel.

[0022] Step ii) can be carried out using one or more ovens, in particular one or more infrared ovens.

[0023] Step iii) may be performed by applying the dry impregnated tape directly around the one or more elongate conductive elements, or around an inner layer of the cable, which itself surrounds the one or more elongate conductive elements.

[0024] Step iii) of applying a dry impregnated tape around the cable comprising at least one elongated conductive element may be performed by wrapping the dry impregnated tape around the cable.

[0025] The wrapping may be longitudinal (ie along the longitudinal axis of the cable or in other words in the direction of the length of the cable) or helical, and is preferably longitudinal.

[0026] The longitudinal wrapping can also be carried out with an overlapping region, the overlapping region or regions accounting for from about 10% to 20%.

[0027] Step iii) can be performed manually or automatically, and is preferably performed automatically.

[0028] Step iii) can be performed by passing the dried impregnated tape through a restriction device or a tape forming device (also indicated by the terms "trumpet" or "tape forming"). During step iii), the cable comprising at least one elongated conductive element is also passed through a restriction device. This device is a mechanical device that continuously wraps the dried impregnated tape around the elongated conductive element. Therefore, this can help to wrap the impregnated tape longitudinally around the cable and thus form the composite layer surrounding the elongated conductive element.

[0029] Nonwoven fiber materials

[0030] The nonwoven fibrous material preferably has a pliable, flexible structure.

[0031] The nonwoven fiber material may be selected from cellulosic materials, synthetic organic polymer-based materials, glass fibers and mixtures thereof, and is preferably selected from synthetic organic polymer-based materials.

[0032] The cellulosic material may be chosen from paper, in particular blotting paper; nonwoven materials made from functionalized or non-functionalized cellulose; substrates with a cellular and / or fibrous structure made from natural cellulose acetate fibers.

[0033] The materials based on synthetic organic polymers may be chosen from polymer materials having a porous and / or fibrous matrix of one or more polyolefins, in particular those chosen from homopolymers and copolymers of propylene, homopolymers and copolymers of ethylene, high density polyethylene (HDPE), aromatic polyamides (aramids), polyesters and mixtures thereof.

[0034] According to a preferred embodiment of the present invention, the nonwoven fiber material is polyethylene terephthalate (PET).

[0035] The nonwoven fiber material preferably has a weight of from about 50 to 120 g / cm 2 This provides a composite layer that is flexible enough to allow easy handling, yet strong enough to give good fire protection.

[0036] According to a preferred embodiment of the present invention, the nonwoven fiber material accounts for from about 2 to 95 wt%, particularly preferably from about 5 to 45 wt%, and even more preferably from about 10 to 35 wt%, relative to the total weight of the composite layer.

[0037] Geopolymer compositions

[0038] The geopolymer composition used in step i) is preferably a liquid geopolymer composition.

[0039] The geopolymer composition in step i) is preferably an aluminosilicate geopolymer composition.

[0040] The geopolymer composition of the present invention is particularly preferably a geopolymer composition comprising water, silicon (Si), aluminum (Al), oxygen (O) and at least one element selected from potassium (K), sodium (Na), lithium (Li), cesium (Cs) and calcium (Ca), and preferably selected from potassium (K) and sodium (Na).

[0041] The geopolymer composition may specifically comprise at least one first aluminosilicate, at least one first alkali silicate, water and optionally an alkali base.

[0042] In the present invention, the geopolymer composition is a precursor composition of a geopolymer. In other words, it comprises ingredients (a first aluminosilicate, at least one first alkali silicate, water and optionally an alkali base; or a first metakaolin, a second metakaolin, a first alkali silicate, water and optionally an alkali base and / or a second alkali silicate, as defined below) that are geopolymerized together (by polycondensation) to form a geopolymer (also called geopolymer material, as defined below).

[0043] First Aluminosilicate

[0044] The first aluminosilicate may be selected from metakaolin (ie calcined kaolin), fly ash, blast furnace slag, expanded clays such as bentonite, calcined clay, any type of compound comprising aluminum and fumed silica, zeolites, and mixtures thereof.

[0045] Among these compounds, preference is given to metakaolins, in particular those sold by the company Imérys.

[0046] In the present invention, the expression "metakaolin" means calcined kaolin or dehydroxylated aluminosilicate. It is preferably obtained by dehydration of kaolin or kaolinite. This dehydration is conventionally obtained by calcination.

[0047] The geopolymer composition may comprise from about 5 to 50 wt% aluminosilicate, and preferably from about 10 to 35 wt% aluminosilicate, relative to the total weight of the geopolymer composition.

[0048] The geopolymer composition may further comprise a second aluminosilicate different from the first aluminosilicate.

[0049] Preferably, the geopolymer composition comprises two calcined kaolins having different calcination temperatures.

[0050] According to a particularly preferred embodiment of the present invention, the geopolymer composition comprises a polymer selected from the group consisting of polymers having a temperature T of at least about 650°C. c1 The first metakaolin selected from the kaolin calcined at temperature T c2 (so that T c2 -T c1 ≥ about 100° C.), at least one first alkaline silicate, water and optionally an alkaline base. The geopolymer composition can then have improved mechanical properties, in particular in terms of flexibility and durability, while ensuring good reaction and fire resistance properties.

[0051] Since the second metakaolin is selected from the c2 (so that T c2 -T c1 ≥ about 100° C.), so it is different from the first metakaolin defined in the present invention.

[0052] According to one embodiment of the present invention, the first metakaolin is a calcined clay having a temperature T of at least about 700°C and preferably at least about 725°C. c1 Calcined kaolin.

[0053] According to a preferred embodiment of the present invention, the first metakaolin is at a temperature T of at most about 875°C and preferably at most about 825°C. c1 Calcined kaolin.

[0054] The first metakaolin may include at least about 20 mol %, and preferably at least about 30 mol %, of aluminum oxide (Al 2 O 3 ), relative to the total moles of the first metakaolin.

[0055] The first metakaolin may contain up to about 60 mol %, and preferably up to about 50 mol %, of aluminum oxide (Al 2 O 3 ), relative to the total moles of the first metakaolin.

[0056] The first metakaolin may include at least about 35 mol %, and preferably at least about 45 mol %, of silicon oxide (SiO 2 ), relative to the total moles of the first metakaolin.

[0057] The first metakaolin may contain up to about 75 mol %, and preferably up to about 65 mol %, of silicon oxide (SiO 2 ), relative to the total moles of the first metakaolin.

[0058] As an example of a first metakaolin we may mention the metakaolin sold by the company Ingela, in particular under the reference no. 450 kaolin for sale.

[0059] The first metakaolin may be selected from T c1 The kaolin is calcined at 400 °C for a period of at least about 1 min, preferably at least about 10 min, particularly preferably from about 30 min to 8 h, and more particularly preferably from about 2 h to 6 h.

[0060] The second metakaolin is preferably selected from c2 The calcined kaolin makes T c2 -T c1 ≥ about 150°C, especially preferably making T c2 -T c1 ≥ about 200°C, and more particularly preferably such that T c2 -T c1 ≥ about 250℃.

[0061] According to one embodiment of the present invention, the second metakaolin is prepared at a temperature T of at least about 800° C., preferably at least about 850° C., and particularly preferably at least about 900° C. c2 Calcined kaolin.

[0062] According to a preferred embodiment of the present invention, the second metakaolin is a calcined clay having a temperature T of at most about 1200°C and preferably at most about 1150°C. c2 Calcined kaolin.

[0063] The second metakaolin may include at least about 20 mol %, and preferably at least about 30 mol %, of aluminum oxide (Al 2 O 3 ), relative to the total moles of the second metakaolin.

[0064] The second metakaolin may contain up to about 60 mol %, and preferably up to about 50 mol %, of aluminum oxide (Al 2 O 3 ), relative to the total moles of the second metakaolin.

[0065] The second metakaolin may contain at least about 35 mol %, and preferably at least about 45 mol %, of silicon oxide (SiO 2 ), relative to the total moles of the second metakaolin.

[0066] The second metakaolin may contain up to about 75 mol %, and preferably up to about 65 mol %, of silicon oxide (SiO 2 ), relative to the total moles of the second metakaolin.

[0067] As an example of a second metakaolin we may mention the metakaolin sold by the company Ingela, in particular under the reference 200R sells kaolin.

[0068] The second metakaolin may be selected from T c2 The kaolin is calcined at 400 °C for a period of at least about 1 min, preferably at least about 5 min, particularly preferably from about 10 min to 2 h, and more particularly preferably from about 15 min to 1 h.

[0069] The weight ratio [first metakaolin / second metakaolin] in the geopolymer composition preferably ranges from about 0.1 to 2, particularly preferably from about 0.5 to 1.0, and more particularly preferably about 1.

[0070] The geopolymer composition may comprise from about 5 to 50 wt%, and preferably from about 10 to 35 wt%, of the first and second metakaolins relative to the total weight of the geopolymer composition.

[0071] The crystallinity of the samples can be determined by differential thermal analysis (DTA) [the presence or absence of crystallization points or peaks], nuclear magnetic resonance (NMR) [ 27 Al spectroscopy] and / or X-ray diffraction (XRD) analysis of the first and second metakaolins.

[0072] The first metakaolin preferably has a crystallization peak in differential thermal analysis, particularly preferably at a temperature of from 900°C to 1060°C, and more particularly preferably at a temperature of from 950°C to 1010°C.

[0073] The second metakaolin preferably comprises mullite.

[0074] The first alkaline silicate

[0075] The first alkaline silicate may be selected from sodium silicate, potassium silicate and mixtures thereof.

[0076] Preference is given to alkaline silicates sold by the company Silmaco or the company PQ. The first alkaline silicate is preferably sodium silicate.

[0077] The first alkaline silicate may have a molar ratio SiO2 / M2O of from about 1.1 to 35, preferably from about 1.3 to 10, and particularly preferably from about 1.4 to 5, wherein M is a sodium atom or a potassium atom, and preferably a sodium atom.

[0078] The geopolymer composition may comprise from about 5 to 60 wt %, and preferably from about 10 to 50 wt %, of the first alkaline silicate, relative to the total weight of the geopolymer composition.

[0079] Second alkaline silicate

[0080] The geopolymer composition may further comprise a second alkali silicate different from the first alkali silicate.

[0081] The second alkaline silicate may be selected from sodium silicate, potassium silicate and mixtures thereof. Preferably, the alkaline silicate is sold by Silmaco or PQ. Preferably, the second alkaline silicate is sodium silicate.

[0082] The first and second alkaline silicates may have molar ratios SiO2 / M2O and SiO2 / M'2O, respectively, such that the same M and M' are selected from sodium atoms and potassium atoms, and preferably sodium atoms, and the ratios have different values, preferably such that their difference is at least 0.3, particularly preferably such that their difference is at least 0.5, and more particularly preferably such that their difference is at least 1.0.

[0083] According to one embodiment of the present invention, the geopolymer composition comprises:

[0084] - a first alkaline silicate having a molar ratio SiO2 / M2O of from about 1.5 to 2.6, and

[0085] a second alkaline silicate having a molar ratio SiO2 / M'2O greater than 2.6, preferably from about 2.8 to 4.5 and particularly preferably from about 3.0 to 4.0, it being understood that M' is identical to M.

[0086] The geopolymer composition may comprise from about 10 to 60 wt %, and preferably from about 20 to 50 wt %, of the first and second alkali silicates relative to the total weight of the geopolymer composition.

[0087] The weight ratio [first alkali silicate / second alkali silicate] in the geopolymer composition preferably ranges from 0.5 to 2.5 and particularly preferably from 0.8 to 2.0.

[0088] Alkaline Base

[0089] The alkaline base may be sodium hydroxide or potassium hydroxide, and preferably sodium hydroxide.

[0090] The geopolymer composition may be free of alkaline bases. This may improve the handling of the geopolymer composition, in particular during the preparation of the cable.

[0091] The solids / water weight ratio in the geopolymer composition determines the setting kinetics in steps i) to iii).

[0092] The geopolymer composition may comprise from about 35 to 80 wt % and particularly preferably from about 40 to 70 wt % of solid materials (alkali silicate(s), aluminosilicate(s) and alkali base) relative to the total weight of the geopolymer composition.

[0093] The geopolymer composition may further comprise one or more additives selected from:

[0094] -dye,

[0095] - mineral fibers, in particular chosen from alumina fibers,

[0096] an additive having a polymer structure, in particular chosen from polyolefin fibers, such as polypropylene fibers, high-density polyethylene (HDPE), polyaramids and technical glass fibers coated with silicone or with organic polymers of the polyethylene type; styrene-butadiene copolymers (SBR); styrene-butadiene-ethylene copolymers (EBS); derivatives of styrene-ethylene copolymers, in particular those sold by Kraton, such as copolymers of styrene-ethylene-butylene-styrene (SEBS), styrene-butadiene-styrene copolymers (SBS), styrene-isoprene-styrene copolymers (SIS), styrene-propylene-ethylene copolymers (EPS) or styrene-ethylene-propylene-styrene copolymers (SEPS); ethylene / vinyl acetate copolymers (EVA), polyorganosiloxanes that have been crosslinked (for example with the aid of peroxides); polyethylene, optionally in powder form; lignin sulfonates; cellulose acetate; other cellulose derivatives; low-viscosity silicone oils (for example of the order of 12500 cP); and polyethylene oils,

[0097] - a compound promoting agglomeration, in particular selected from aluminum sulfate, alum (for example potassium aluminum sulfate double salt), calcium chloride, calcium sulfate, hydrated calcium sulfate, sodium aluminate, sodium carbonate, sodium chloride, sodium silicate, sodium sulfate, iron (III) chloride and sodium lignin sulfonate,

[0098] - caking retarders, in particular selected from ammonium, alkali metals, alkaline earth metals, borax, metal salts of lignin sulfonates and in particular calcium lignin sulfonates, celluloses such as carboxymethylhydroxyethylcellulose, sulfoalkylated lignins such as, for example, sulfomethylated lignins, hydroxycarboxylic acids, copolymers of salts of 2-acrylamido-2-methylpropanesulfonic acid with salts of acrylic acid or maleic acid, and saturated salts,

[0099] - inert fillers, in particular chosen from talc, mica, dehydrated clay and calcium carbonate,

[0100] -starch,

[0101] - starch plasticizers, in particular chosen from metal stearates, polyethylene glycols, ethylene glycol, polyols such as glycerol, sorbitol, mannitol, maltitol, xylitol or oligomers of one of these polyols, sucrose such as glucose or fructose, plasticizers containing amide groups, and any type of plasticizer based on one or more modified polysaccharides,

[0102] - cellulose derivatives,

[0103] - Expanded carbonaceous materials, such as expanded graphite.

[0104] The dye is preferably a dye that is liquid at room temperature (ie at 18°C ​​to 25°C).

[0105] The geopolymer composition may comprise up to about 15 wt% of one or more additives, preferably up to about 8 wt% of one or more additives and particularly preferably up to about 5 wt% of one or more additives, relative to the total weight of the geopolymer composition.

[0106] According to a particularly preferred embodiment of the present invention, the geopolymer composition comprises at most about 15 wt% of one or more organic additives such as one or more organic polymers, preferably at most about 8 wt% of one or more organic additives such as one or more organic polymers, and particularly preferably at most about 5 wt% of one or more additives such as one or more organic polymers, relative to the total weight of the geopolymer composition.

[0107] The geopolymer composition may comprise at least about 0.01 wt% of one or more additives, and preferably at least about 0.5 wt% of one or more additives, relative to the total weight of the geopolymer composition.

[0108] Composite layer

[0109] The composite layer is preferably an electrically insulating layer.

[0110] In the present invention, "electrically insulating layer" means a layer whose electrical conductivity may be at most 1.10 -9S / m, and preferably at most 1.10 -10 S / m (Siemens / meter) (at 25°C).

[0111] The composite layer is preferably a flame retardant and / or fire resistant layer.

[0112] The composite layer preferably has a thickness of from about 0.2 to 3 mm, and particularly preferably from about 0.5 to 1 mm.

[0113] When the thickness of the composite layer is less than 0.2 mm, the thermal protection of the cable obtained according to the method of the present invention is insufficient.

[0114] The composite layer of the present invention is preferably a tape-like layer (ie in the form of a tape or strip).

[0115] The composite layer preferably has an approximately constant thickness and in particular forms a continuous protective shell.

[0116] The composite layer may in particular comprise 2 to 3 superposed tapes.

[0117] The composite layer of the present invention is preferably not porous.

[0118] The composite layer is preferably an inner layer of the cable.

[0119] According to the present invention, "inner layer" means a layer which does not constitute the outermost layer of the cable.

[0120] The composite layer preferably comprises at least one geopolymer material and a nonwoven fibrous material as defined in the present invention.

[0121] Geopolymer Materials

[0122] In the present invention, the geopolymer material is obtained from a geopolymer composition as defined in the present invention, preferably by hardening, geopolymerization and / or polycondensation of said geopolymer composition.

[0123] In particular, the geopolymer composition as defined in the present invention is capable of forming said geopolymer material. Thus, the components of the geopolymer composition can undergo polycondensation to form said geopolymer material. Hardening occurs by an internal reaction of the polycondensation type. Hardening is not, for example, the result of simple drying, as is usually the case with binders based on alkali silicates.

[0124] In fact, geopolymer materials result from a mineral polycondensation reaction (known as geosynthesis) carried out by alkali activation, in contrast to conventional hydraulic binders where the hardening is the result of the hydration of calcium aluminates and calcium silicates.

[0125] In the present invention, the expression "geopolymer material" refers to a solid material comprising silicon (Si), aluminum (Al), oxygen (O) and at least one element selected from potassium (K), sodium (Na), lithium (Li), cesium (Cs) and calcium (Ca), and preferably selected from potassium (K) and sodium (Na).

[0126] The geopolymer material may be an aluminosilicate geopolymer material.

[0127] Aluminosilicate geopolymer materials may be selected from the group consisting of n (-Si-O-Al-O-) n [(M)-PS] and a poly(aluminosilicate) having a molar ratio Si / Al equal to 1, corresponding to formula (II) M n (-Si-O-Al-O-Si-O-) n [(M)-PPS] poly(aluminosilicate-silicon oxide) having a molar ratio Si / Al equal to 2, corresponding to formula (III) M n (-Si-O-Al-O-Si-O-Si-O) n [(M)-PSDS] and a poly(aluminosilicate-disiloxane) with a molar ratio Si / Al equal to 3, and other poly(aluminosilicates) wherein the ratio Si / Al>3, the above poly(aluminosilicates) containing a basic cation M selected from K, Na, Li, Cs and mixtures thereof, and n represents the degree of polymerization.

[0128] In one embodiment, the geopolymer material comprises from about 5 to 98 wt%, preferably from about 55 to 95 wt%, and more preferably from about 65 to 90 wt%, relative to the total weight of the composite layer.

[0129] The method may further comprise, before step i), a step i0) of preparing a geopolymer composition comprising a mixture of the first aluminosilicate and the first alkali silicate, water and optionally an alkali base.

[0130] Step i0) is generally carried out at a high pH, ​​in particular in the range from 10 to 13.

[0131] Step i0) preferably comprises the following sub-steps:

[0132] i 01 ) a sub-step of preparing an aqueous solution of a first alkaline silicate, and

[0133] i 02 ) the first aluminosilicate in powder form is mixed with the 01 ) in a sub-step of mixing the aqueous solution of the alkaline silicate prepared in ).

[0134] The first aqueous solution of the alkaline silicate can be prepared by mixing silicon dioxide SiO2 or an alkaline silicate with a base MOH wherein M is K or Na.

[0135] The silicon dioxide SiO2 may be selected from fumed silica (ie, pyrogenic silica), quartz, and mixtures thereof.

[0136] Sub-step i 01 ) can be carried out by dissolving the base in water, resulting in the release of heat (exothermic reaction), and then adding the silicon dioxide (or alkaline silicate). The released heat then accelerates sub-step i 01 ) dissolving silicon dioxide (or alkaline silicate), and sub-step i 02 ) in the dissolution of the first aluminosilicate.

[0137] When a second aluminosilicate and / or a second alkali silicate as defined in the present invention is present, step i0) of preparing the geopolymer composition may comprise mixing said first aluminosilicate, preferably in powder form, and optionally said second aluminosilicate, preferably in powder form, with said first alkali silicate, preferably in aqueous solution, optionally said second alkali silicate, preferably in aqueous solution.

[0138] Step i0) preferably comprises mixing the first and second metakaolin clays with the first alkali silicate and optionally the second alkali silicate, water and optionally an alkaline base.

[0139] The first and second metakaolins and the first and second alkali silicates are as defined in the present invention.

[0140] According to a preferred embodiment, step i0) comprises the following sub-steps:

[0141] i 0a ) mixing the first and second alkaline silicates (preferably in aqueous solution), in particular under stirring,

[0142] i 0b ) optionally adding an alkaline base, particularly while maintaining stirring, and

[0143] i 0c ) adding the first and second metakaolin clays (preferably in powder form), particularly while maintaining stirring.

[0144] In step i0) or sub-step i 02 ) or i 0c ) at the end of the step, a homogeneous solution of the fluid is preferably obtained.

[0145] At the end of step i0), the geopolymer composition may comprise from about 35 to 80 wt % and particularly preferably from about 40 to 70 wt % of solid materials (alkali silicate(s), aluminosilicate(s) and alkali base) relative to the total weight of said geopolymer composition.

[0146] This weight ratio may provide a geopolymer composition which is sufficiently fluid to allow it to be handled and which has sufficiently slow setting kinetics to allow the formation of a cable layer as defined below.

[0147] The solid / water weight ratio in the geopolymer composition may enable the setting kinetics of the geopolymer composition to be determined.

[0148] After step i0) of preparing the geopolymer composition and before the impregnation step i), the geopolymer composition may be heated, in particular to a temperature of from about 55 to 95° C. and particularly preferably from about 70 to 90° C. This will thus facilitate step i).

[0149] The method may further comprise, after step iii), a step iv) of applying an outer protective sheath around the composite layer. The outer protective sheath may ensure the mechanical integrity of the cable.

[0150] At the end of step iv), the cable may then comprise at least one elongated conductive element, a composite layer surrounding said elongated conductive element, and at least one outer protective sheath surrounding said composite layer.

[0151] Step iv) is preferably carried out by extrusion, in particular at a temperature of from about 140°C to 195°C.

[0152] Step iv) can be carried out using an extruder.

[0153] In this embodiment, the extrusion head may be positioned at the outlet of the forming device as defined in the present invention.

[0154] The outer protective sheath is preferably the outermost layer of the cable.

[0155] The outer protective sheath is preferably an electrically insulating layer.

[0156] The outer protective sheath is preferably made of a halogen-free material. It can be produced conventionally starting from a flame-retardant or flame-resistant material. In particular, if the latter does not contain halogen, it is referred to as a cladding of the HFFR type (standing for "halogen-free flame retardant").

[0157] The outer protective sheath may comprise at least one organic or inorganic polymer.

[0158] The choice of organic or inorganic polymers is not restricted and they are well known to those skilled in the art.

[0159] According to a preferred embodiment of the present invention, the organic or inorganic polymer is selected from cross-linked and non-cross-linked polymers.

[0160] The organic or inorganic polymers may be homopolymers or copolymers having thermoplastic and / or elastomeric properties.

[0161] The inorganic polymer may be a polyorganosiloxane.

[0162] The organic polymer may be a polyurethane or a polyolefin.

[0163] The polyolefin may be chosen from polymers of ethylene and propylene. As examples of ethylene polymers, we may mention linear low density polyethylene (LLDPE), low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), ethylene / vinyl acetate copolymers (EVA), ethylene / butyl acrylate copolymers (EBA), ethylene / methyl acrylate copolymers (EMA), 2-hexylethyl acrylate (2HEA), copolymers of ethylene and alpha-olefins such as, for example, polyethylene-octene (PEO), copolymers of ethylene and propylene (EPR), terpolymers of ethylene and propylene (EPT) such as, for example, terpolymers of ethylene-propylene-diene monomers (EPDM), or mixtures thereof.

[0164] The polymer of the outer protective sheath is preferably an organic polymer, more preferably an ethylene polymer, and more preferably an ethylene / vinyl acetate copolymer, a linear low density polyethylene or a mixture thereof.

[0165] The outer protective sheath may further comprise a hydrated fire-resistant mineral filler. Such a hydrated fire-resistant mineral filler acts physically, mainly by endothermic decomposition (e.g. release of water), which has the result of reducing the temperature of the sheath and limiting the propagation of flames along the cable. We refer in particular to flame-retardant properties, well known as "flame retardants".

[0166] The hydrated fire retardant mineral filler may be a metal hydroxide, such as magnesium hydroxide or aluminum trihydroxide.

[0167] The outer protective sheath may further comprise an inert filler, in particular selected from talc, mica, dehydrated clay and mixtures thereof.

[0168] Advantageously, the cable obtained by the method according to the invention meets at least one of the criteria for reaction or non-propagation in fire, said standard being chosen from the standards EN 60332-1, EN 60332-3 and EN 50399 (2012 / 02+A1 2016); and preferably the standard EN 50399 (2012 / 02+A1 2016), in particular the classification criteria B2ca, s1a, d0, a1 of said standard, and optionally the standards EN 60332-1 and EN 60332-3.

[0169] According to one embodiment of the invention, the cable is a power cable and / or a telecommunication cable, and preferably an electrical cable.

[0170] When the cable comprises a plurality of elongated conductive elements, the composite layer may then surround the plurality of elongated conductive elements of the cable.

[0171] The cable may comprise a single composite layer as defined in the present invention or a plurality of composite layers as defined in the present invention.

[0172] When the cable comprises a plurality of composite layers, the method may further comprise repeating steps i) to iii) as many times as there are composite layers to be applied, and then optionally repeating step iv) as defined in the present invention.

[0173] Preferably, the cable comprises a single composite layer, and more particularly preferably a single inner composite layer.

[0174] According to one embodiment of the invention, the cable obtained by the method according to the invention further comprises one or more layers interposed between the elongated conductive element as defined in the invention and the composite layer.

[0175] The layers may include one or more polymer layers, such as an electrically insulating polymer layer, and / or one or more metal layers, such as a metal layer comprising one or more holes.

[0176] In this case, the method further comprises one or more steps of applying one or more of the above-mentioned layers around the elongated conductive element, the assembly of elongated conductive elements, or around each of the elongated conductive elements, depending on the type of cable required, before step i) or before step iii).

[0177] The metal layer containing one or more holes is typically a layer used in radiating cables familiar to those skilled in the art.

[0178] According to a preferred embodiment of the present invention, the cable comprises:

[0179] - a plurality of electrically conductive elements, each of said electrically conductive elements being surrounded by a polymer layer, in particular an electrically insulating polymer layer, to form a plurality of insulated electrically conductive elements,

[0180] - a composite layer as defined in the present invention surrounding said plurality of insulated conductive elements, and

[0181] An outer protective sheath surrounding the composite layer, in particular an electrically insulating outer protective sheath.

[0182] The process according to the invention is preferably a continuous process. In other words, at least steps i) to iii), and preferably at least steps i) to iv), are carried out continuously.

[0183] In the present invention, the expression "continuous process" means that the process is carried out on a single production line and / or without a resting, collecting or recovering step. In other words, in the process according to the invention, there is no resting intermediate step between the distribution of the nonwoven fiber material and the recovery / production of the final cable. In other words, furthermore, steps i), ii), iii) and iv) if present are combined, i.e. steps i), ii), iii) and iv) if present are carried out simultaneously.

[0184] According to this embodiment, the nonwoven fiber material may be arranged on a dispenser such as a pay-off device or an unwinder, and the material may be continuously dispensed or unwound for performing at least steps i) to iii) or steps i) to iv).

[0185] Preferably, step i) is carried out by passing the nonwoven fibrous material through a coating device supplied with the geopolymer composition at a flow rate D (in kg / min), the dispenser delivering the nonwoven fibrous material at a speed V (in km / min), and the ratio D / V ranges from about 20 to 50 kg geopolymer composition / km of nonwoven fibrous material, and particularly preferably from about 25 to 40 kg geopolymer composition / km of nonwoven fibrous material. Thus, the amount of geopolymer composition applied to the nonwoven fibrous material can be easily controlled by a pump.

[0186] The speed V is preferably equal to the travel speed of the cable.

[0187] The flow rate D may range from about 0.5 kg / min to 4.5 kg / min.

[0188] The speed V may range from about 20 m / min to 150 m / min.

[0189] According to a particularly preferred embodiment of the invention, the nonwoven fibrous material is passed through a coating device to carry out step i), the impregnated tape obtained is then passed through one or more ovens, preferably through several ovens arranged one after the other in sequence to carry out step ii), the dried impregnated tape is then passed through a tape-forming device, through which a cable comprising at least one elongated conductive element is passed to carry out step iii), and finally the cable obtained is passed through an extruder head in order to carry out step iv).

[0190] In step ii), the transition from the liquid to the pasty state requires a large amount of energy.The use of several ovens enables the drying of the impregnated tape to be optimized (in terms of exposure time, speed V and amount of energy supplied).

[0191] The method according to the invention is rapid, simple and advantageous from an economic point of view. It enables the manufacture in only a few steps of a cable having good mechanical properties, in particular in terms of flexibility and durability, while ensuring good fire resistance.

[0192] The present invention will be better understood and other objects, details, features and advantages of the present invention will become more apparent from the following description of specific embodiments of the present invention, which is given for illustrative purposes only and not limiting, with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0193] The accompanying drawings illustrate the invention:

[0194] Figure 1 Shown is a schematic diagram of a cable as obtained by the method according to the invention.

[0195] Figure 2 A schematic diagram of the method according to the invention is shown.

[0196] For the sake of clarity, only the elements which are essential to the understanding of the invention are shown schematically in these drawings and are not drawn to scale. DETAILED DESCRIPTION

[0197] Figure 1 The cable 100 shown corresponds to a fire-resistant cable of type K25 or RZ1K.

[0198] The cable 100 comprises four elongated conducting elements 10, each of which is insulated with an electrical insulating layer 20, and a composite layer 30 as defined in the present invention surrounding the four elongated insulated conducting elements (10, 20) in sequence and coaxially, and an outer sheath 40 of HFFR type surrounding the composite layer 30 as defined in the present invention and advantageously in the form of a tape.

[0199] Figure 2 is a schematic diagram of a method according to the invention carried out continuously. Specifically, a nonwoven fibrous material 1 in the form of a tape is placed on a winder 2, unwound and introduced to a coating die 3 supplied with a geopolymer composition 4, so as to allow the nonwoven fibrous material 1 to be impregnated with said geopolymer composition [step i)]. The impregnated tape is then conveyed to an oven 5, so as to dry it [step ii)]. The dried impregnated tape is then introduced into a confinement device 6, through which a cable comprising at least one elongated conductive element passes, so as to allow the dried impregnated tape to be longitudinally wrapped around the cable and thus form said composite layer surrounding said elongated conductive element [step iii)], and finally the cable obtained is passed through an extrusion head 7 to form an outer protective sheath [step iv)].

[0200] The following examples provide an illustration of the present invention. They are in no way intended to limit the overall scope of the invention as set forth in the claims.

[0201] The raw materials used in the examples are listed below:

[0202] - about 50% by weight of an aqueous solution of a first sodium silicate, of the "water glass" type, from the company Silmaco, a sodium silicate in which the SiO2 / Na2O molar ratio is about 2.0,

[0203] - an aqueous solution of about 38% by weight of a second sodium silicate, of the "water glass" type, from the company Silmaco, a sodium silicate having a SiO2 / Na2O molar ratio of about 3.4,

[0204] -First Metakaolin, 450, Inge Ceramics, kaolin having an Al2O3 / SiO2 molar ratio of 41 / 55 (i.e., about 0.745) and calcined at a temperature of about 700°C,

[0205] - Second metakaolin, 200R, Inge Ceramics, kaolin calcined at a temperature of about 1000°C, wherein the Al2O3 / SiO2 molar ratio is 41 / 55 (i.e., about 0.745), and

[0206] - Nonwoven polyester material, GT320, GECATAPES.

[0207] Unless otherwise stated, all of these raw materials were used as received from the manufacturers.

[0208] Example 1: Preparation of fire-resistant cable by the method according to the present invention

[0209] The geopolymer composition was prepared as follows: an aqueous solution of alkaline silicate was prepared by mixing 40 g of a 50 wt % first aqueous sodium silicate solution and 40 g of a 38 wt % second aqueous sodium silicate solution. 10 g of the first metakaolin and 10 g of the second metakaolin were then mixed with the aqueous solution of alkaline silicate. The geopolymer composition contained about 55.2 wt % solid material relative to the total weight of the geopolymer composition.

[0210] The nonwoven fibrous polyester material in the form of a tape was placed on a winder, unwound at a speed of about 50 m / min and led to a coating die supplied with the geopolymer composition at a flow rate of 1.25 kg / min to allow the nonwoven fibrous material to be impregnated with the geopolymer composition. The geopolymer composition had a temperature of about 40°C.

[0211] The impregnated tape was then directed to a first IR oven operating at a temperature of 800°C, then to a second IR oven operating at a temperature of 800°C, and finally to a third IR oven operating at a temperature of 800°C, in order to allow drying of the impregnated tape.

[0212] The dry impregnated tape is then introduced into a restraining device through which the low-voltage cable runs so as to allow the impregnated tape to be wrapped longitudinally around the cable. The cable comprises 5 copper conductors of cross-sectional area 1.5 mm2, each surrounded by an electrical insulation layer based on XLPE. At the end of the step of applying the impregnated tape around the cable, a composite layer is obtained that surrounds the insulated conductors.

[0213] The formed composite layer had a thickness of 0.5 mm.

[0214] The assembly obtained is then covered by hot extrusion with a protective polymer sheath based on a mixture HFFR based on polyethylene and fireproof fillers produced by NEXANS, said sheath having a thickness of about 2 mm. A cable according to the invention is thus obtained. The flame retardant properties of the cable are determined according to standard EN 50399. 15 cable segments located on a vertical ladder are exposed to a flame of 20 kW power for 20 min.

[0215] The results are reported in Table 1 below:

[0216]

[0217] Table 1

[0218] In this table, the acronym HRR corresponds to the expression “heat release rate,” which indicates the heat flow rate, the acronym THR corresponds to the expression “total heat release,” which indicates the amount of heat released during combustion, the acronym FIGRA corresponds to the expression “fire growth rate,” which indicates the growth rate of fire, the acronym SPR corresponds to the expression “smoke generation rate,” which indicates the generation rate of smoke, and the acronym TSP corresponds to the expression “total smoke generation,” which indicates the total amount of smoke generated.

[0219] These results demonstrate that, with regard to the requirements of European standard EN 50399, the cable according to the invention exhibits maximum fire protection properties.

Claims

1. A method for manufacturing a cable, the cable comprising at least one elongated conductive element and at least one composite layer surrounding the elongated conductive element, characterized in that The method comprises at least the following steps: i) impregnating a non-woven fiber material with a geopolymer composition so as to form a belt impregnated with said geopolymer composition, ii) drying the impregnated tape obtained in step i) to form a dried impregnated tape, and iii) applying said dried impregnated tape obtained in step ii) around a cable comprising at least one elongated conductive element so as to form said composite layer surrounding said elongated conductive element.

2. The method according to claim 1, characterized in that The nonwoven fibrous material is selected from the group consisting of cellulosic materials, synthetic organic polymer-based materials, glass fibers, and mixtures thereof.

3. The method according to claim 1, characterized in that The geopolymer composition is an aluminosilicate geopolymer composition.

4. The method according to claim 1, characterized in that: Step i) is carried out by coating impregnation.

5. The method according to claim 1, characterized in that: Step i) is performed by passing the nonwoven fibrous material through a coating device supplied with the geopolymer composition.

6. The method according to claim 1, characterized in that Step ii) is carried out at a temperature of at most 120°C.

7. The method according to claim 1, characterized in that Step ii) is carried out at a temperature of at least 50°C.

8. The method according to claim 1, characterized in that Step iii) of applying said dry impregnated tape around a cable comprising at least one elongated conductive element is performed by wrapping said dry impregnated tape around said cable.

9. The method according to claim 8, characterized in that The wrapping is longitudinal.

10. The method according to claim 1, characterized in that Step iii) is performed by passing the dried impregnated tape through a restriction device.

11. The method according to claim 1, characterized in that: The method further comprises, after step iii), the step iv) of applying an outer protective sheath around the composite layer.

12. The method according to claim 11, characterized in that Step iv) is carried out by extrusion.

13. The method according to claim 1, characterized in that The process is a continuous process.

14. The method according to claim 13, characterized in that The nonwoven fibrous material is arranged on a dispenser and the material is continuously dispensed for performing at least steps i) to iii).

15. The method according to claim 14, characterized in that Step i) is carried out by passing the nonwoven fibrous material at a flow rate D (in kg / min) through a coating device supplied with the geopolymer composition, the dispenser delivering the nonwoven fibrous material at a speed V (in km / min), and the ratio D / V ranges from 20 to 50 kg geopolymer composition / km nonwoven fibrous material.